2018
DOI: 10.1016/j.jot.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum copper levels are associated with bone mineral density and total fracture

Abstract: BackgroundBoth copper deficiency and overexposure have been associated with adverse health effects. Evidence linking copper to bone mineral density (BMD) and total fracture, however, is limited.MethodsThis nationally representative cross-sectional study enrolled participants from the National Health and Nutrition Examination Survey (2011–2014) in the United States. Using unadjusted and multivariate adjusted logistic regression analyses and a two-piecewise linear regression model with a smoothing function, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…In general, moderate copper levels are essential for normal growth, development, health, such as the normal functioning of innate immune system (Djoko et al, 2015;Bost et al, 2016), and bone health (Eaton-Evans et al, 1996;Qu et al, 2018). Of note, copper is also vital for maintenance of integrity and homeostasis of cartilage tissues.…”
Section: Chondroprotective Effects Of Copper In Cartilagementioning
confidence: 99%
“…In general, moderate copper levels are essential for normal growth, development, health, such as the normal functioning of innate immune system (Djoko et al, 2015;Bost et al, 2016), and bone health (Eaton-Evans et al, 1996;Qu et al, 2018). Of note, copper is also vital for maintenance of integrity and homeostasis of cartilage tissues.…”
Section: Chondroprotective Effects Of Copper In Cartilagementioning
confidence: 99%
“…As previously mentioned, this element is necessary for the synthesis of Cu-Zn SOD, and its deficit could increase muscle damage as a result of OS. Regarding bone mass, it has been reported that a Cu deficiency reduces bone mineralization [33]. This mineral is a cofactor in the enzyme lysyl oxidase, which strengthens collagen and bone fibers [34].…”
Section: Discussionmentioning
confidence: 99%
“…Cu deficiency is rare due to the high availability of this element in food [170]. Cu deficiency may lead to pancytopenia and the occurrence of hypodermic anemia which does not respond to the administration of Fe [171,172], loss of appetite [173], damage to internal organs [174,175], bone deformities [176], reduced reproductive capacity [177], myocardial fibrosis [178,179], and chronic debilitating diarrhea [180]. It may lead to neurological disorders, and hair depigmentation [181,182].…”
Section: Copper (Cu)mentioning
confidence: 99%